PARENTING ISLAM DI ERA DIGITAL: KAJIAN KONSEPTUAL MODEL PENGASUHAN TAWAZUN - MASLAHAH - Umi Zulfa (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Keagamaan Islam UNUGHA Cilacap, 2025)
The digital era presents both opportunities and challenges for child upbringing in the Islamic perspective. Previous studies have mostly emphasized the threats of technology, while research that integrates Qur’anic principles with adaptive strategies in the digital space remains limited. This study aims to formulate a conceptual model of Islamic parenting in the digital era that preserves children’s innate nature (fitrah), morals, and worship orientation. The research employed a library research approach with qualitative analysis based on a synthesis of literature from books, scholarly journals, and relevant documents. Data were analyzed using content analysis to identify concepts, challenges, principles, and strategies of Islamic parenting relevant to technological developments. The findings reveal that Islamic parenting in the digital era is a child-rearing process grounded in the values of the Qur’an and Sunnah with contextual adjustments to technological advancements, enabling technology to serve as a medium for faith-based education. Identified challenges include exposure to content contrary to Sharia, risks of digital addiction, degradation of family communication quality, and weak Islamic digital literacy. Five main strategies are proposed: contextual application of Qur’anic principles, building tech-life balance, cultivating digital khushu’, establishing an Islamic Digital Literacy Center, and strengthening supervision and Islamic role modeling in the digital space. In conclusion, this study introduces the Tawazun–Maslahah Parenting Model as a comprehensive and adaptive framework for Islamic parenting in the digital era, offering practical implications for parents in guiding children’s digital engagement, for educators in integrating Islamic digital literacy into learning environments.